Social Isolation, Cognitive Function, and Depression Among Chinese Older Adults: Examining Internet Use as a Predictor and a Moderator - Li, Yunjun; Bai, Xiao; Chen, Honglin (Frontiers in Public Health, 2022)
Objectives: Despite the theoretical and practical interest in Internet use among older adults, evidence examining the impacts of Internet use on late-in-life health is limited. This study examines how Internet use affects depression and cognitive function in older adults and investigates if Internet use moderates the relationship between social isolation and depression/cognitive function. Method: We performed regression analyses using data came from the second wave of the China Longitudinal Aging Social Survey of 2016. Our final sample featured 8,835 older adults. Results: The results show 11.4% of older Chinese adults often used the Internet to engage in at least one activity. Internet use was negatively associated with depression, but it was positively related to cognitive function. Socially isolated older adults were more likely to have more depressive symptoms and higher level of cognitive function. There was also an interaction effect between Internet use and social isolation on depression/cognitive function. The negative effect of social isolation was stronger for older adults who used the Internet less. The moderating effect of Internet use was significant for both males and females. However, among those who used the Internet more, the depression levels of socially isolated male participants was much lower than female participants. Conclusions: Our results reveal the importance of considering Internet use in buffering the negative effects of social isolation and the associated health burdens for aging populations. Recommendations for service practice and future research are discussed.